Taking Responsibility for Academic Integrity: A collaborative teaching and learning design - East, Julianne; Donnelly, Lisa (Journal of University Teaching and Learning Practice, 2012)
La Trobe University, like many Australian universities, states that it values honest academic endeavour (Academic Integrity Policy 2011), and it can provide examples of good teaching practice in the areas of academic integrity, proper acknowledgment and avoiding plagiarism. Rather than relying on the chance that individuals will just develop good practices, this university has recently taken a more systematic approach to teaching students and staff about academic integrity and providing resources to ensure a consistent message and application of acknowledgment conventions. This systematic approach was made possible through the University’s curriculum reform program, the Design for Learning. By positioning academic integrity and acknowledgment as issues of curriculum, La Trobe has created an educational opportunity and reduced the focus on punishment. Furthermore, the mandate to deliver academic integrity programmes to all commencing students and staff and to provide consistent guidelines supports the development of awareness that academic integrity is a whole of university responsibility – everybody’s responsibility. This paper reviews one university’s progress towards aligning academic integrity, with the intention to inform those who are interested in developing an integrated academic integrity education.